Employment Practice of Persons with Disabilities and a Reduced Work Capacity in the Open Labour Market - Balázs-Földi, Emese (International Journal of Engineering and Management Sciences, 2016)
Based on the labour market situation of persons with disabilities and a reduced work capacity as an employee group we can claim that it is an employee group struggling with significant disadvantages. Their economic activity is behind thereof the population without disabilities and a reduced work capacity. According to the latest statistical data the employment level of persons with disabilities and a reduced work capacity is only around 18 per cent. The governments in power try to increase the economic activity of the affected employee group with both positive and negative incentive system laying stress on the field of primary open labour market. However, it is all unimaginable without changing the approach of the society and the business sphere, which can succeed through the legal regulation of equal opportunities, equal treatment and the prohibition of discrimination. By means of professional interviews carried out with company directors and HR directors of 3 examined companies operating in the Northern Great Plain region as well as case studies the article aims at exploring the attitude of market participants towards the employee group of persons with disabilities and a reduced work capacity, legal changes of recent years, the extent this group is employed and the obstacles that make their further employment more difficult.